The Effect of the Use of Authentic Reading Materials in Teaching English on Eleventh Grade EFL Students’ Motivation - Baniabdelrahman, Abdallah (Jordan Journal of Educational Sciences, 2005)
This study investigated the effect of using English language authentic reading materials in teaching English on EFL students’ motivation. The sample consisted of two eleventh grade sections. One was randomly assigned as the control group (37 students) and the other was assigned as the experimental group (35 students). Then students’ motivation level was measured against a self-reported learner motivation questionnaire. The data were analyzed via factorial ANOVA repeated-measures factors and between-groups factors. The results of the study revealed a significant increase in the EFL students’ motivation across time in both of the experimental and control groups. Moreover, the results revealed significant differences between the two groups after 12 weeks of treatment in favor of the experimental group. Based on the results of the study, more studies are recommended to be carried out in different situations for a more thorough investigation.